2023
DOI: 10.1039/d2cc06214c
|View full text |Cite
|
Sign up to set email alerts
|

A porous Ti-based metal–organic framework for CO2photoreduction and imidazole-dependent anhydrous proton conduction

Abstract: Anhydrous proton conductivity of Im@IEF-11 resulting from the integration of imidazole and porous IEF-11 has been investigated, and the highest proton conductive value can reach up to 7.64 × 10-2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The characteristic absorption peaks of Im@ZrSQU (Figure S1b) and Cu@ZrSQU (Figure S2b) at 641 and 761 cm –1 originate from the stretching vibration of the Zr–O bond, which is the characteristic structure of ZrSQU. The characteristic peaks in the spectra of Im@ZrSQU at 1062 and 1323 cm –1 are from the stretching vibration of C–N in Im, and the absorption peak at 1602 cm –1 is from the stretching vibration of CN in Im . The results indicate that the Im molecules have been successfully loaded into the pores of ZrSQU.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The characteristic absorption peaks of Im@ZrSQU (Figure S1b) and Cu@ZrSQU (Figure S2b) at 641 and 761 cm –1 originate from the stretching vibration of the Zr–O bond, which is the characteristic structure of ZrSQU. The characteristic peaks in the spectra of Im@ZrSQU at 1062 and 1323 cm –1 are from the stretching vibration of C–N in Im, and the absorption peak at 1602 cm –1 is from the stretching vibration of CN in Im . The results indicate that the Im molecules have been successfully loaded into the pores of ZrSQU.…”
Section: Resultsmentioning
confidence: 94%
“…The XPS spectra of Im@ZrSQU-200 (Figure S8a) and Cu@ZrSQU-90 (Figure S8b) confirmed that Im@ZrSQU-200 contains C, O, Zr, and N elements, and Cu@ZrSQU-90 contains C, O, Zr, and Cu elements, respectively. In Im@ZrSQU-200, the high-resolution C 1s XPS spectra (Figure S9a) showed three main peaks, which are characteristic signals of square ligands in ZrSQU with characteristic peaks at binding energies of 283.2, 284.6, and 287.1 eV, corresponding to the presence of C–C, C–O, and CO, respectively . The signal at 530.1 eV in the high-resolution O 1s XPS spectrum (Figure S9b) corresponds to the Zr–O bond in ZrSQU, and the other two signals are from the C–O and CO bonds .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations